The Effect Of Product Quality On Consumer Satisfaction Of Balobo Salted Fish In Dobo City, Aru Islands Regency - Geradin Rehatta (CV Putra Publisher, 2022)
This study aims to determine the effect of product quality on consumer satisfaction of salted balobo fish in Dobo City, Aru Islands Regency. The research method used in this research is descriptive quantitative. Analysis of the data used is simple linear regression which is processed using the SPSS program. The population of this research is all buyers or consumers of balobo fish in Dobo City, Aru Islands Regency. The sample of this research was taken by using purposive sampling method as many as 50 respondents. The results of the study prove that the hypothesis is accepted, that product quality which includes shape, durability, style, design, adjustment, aesthetics and convenience has a positive effect on consumer satisfaction with the value of Sig. of 0.000 <0.05, and the value of R2 / coefficient of determination of 0.730 or 73% of the consumer satisfaction variable can be explained by the product quality variable.